Consumer perception of Brazilian beef: insights from a quantitative study in Europe - Timmermann, Jonas Christopher (2016)
Brazilian beef companies have been very successful in recent years due to a range of external factors. These factors include a favourable climate in Brazil and an abundant supply of natural resources (such as supply of water and cheap farmable land). Economically wise, Brazilian beef companies benefitted from cheap labour, reduced trade barriers and a favourable exchange rate. To investigate the quality perception of Brazilian beef, a quantitative study was conducted with German, French and Italian consumers. The results reveal that Brazilian beef lacks brand equity: Respondents that have never bought (or experienced) Brazilian beef have subconsciously a negative impression of the quality of Brazilian beef. Moreover, the image of Brazil as a country has an effect on how consumers perceive Brazilian beef. This paper suggests that Brazilian beef companies should intensify their marketing efforts and invest in the brand building of Brazilian beef. Since the beef industry is important to Brazil’s GDP, the government (supported by ABIEC) is advised to support these marketing programs as well. Brand building serves as a form of protection against times when external factors may worsen.